1977
DOI: 10.1136/hrt.39.8.889
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal survey of ischaemic heart disease in randomly selected sample of older population.

Abstract: A group of 215 men and 272 women aged 62 to 90foming a randomly-selected sample of the older population was studied by cardiovascular survey methods andfollowedfor 5 years. The 5-year mortality of 28 per cent was related to age and was higher in men. Ischaemic heart disease was the certified cause of 28 per cent of the deaths. Mortality was greater in those with systolic hypertension. Among electrocardiographic features ST depression, T inversion, and atrial fibrillation increased overall and ischaemic heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…A recent study in the United States, however, reported prevalences of 0.3% in people aged 65-69, 1.5% in those aged 70-79, and 3% in those aged over 80 30. The higher mortality from cerebrovascular and cardiovascular disease in the United Kingdom would suggest that atrial fibrillation may be more prevalent here, but British studies of prevalence have involved small numbers of elderly patients from unrepresentative populations 33 34 35 36 37 38. Best estimates are therefore based on the Australian and North American studies.…”
Section: Prevalence Of Atrial Fibrillationmentioning
confidence: 86%
“…A recent study in the United States, however, reported prevalences of 0.3% in people aged 65-69, 1.5% in those aged 70-79, and 3% in those aged over 80 30. The higher mortality from cerebrovascular and cardiovascular disease in the United Kingdom would suggest that atrial fibrillation may be more prevalent here, but British studies of prevalence have involved small numbers of elderly patients from unrepresentative populations 33 34 35 36 37 38. Best estimates are therefore based on the Australian and North American studies.…”
Section: Prevalence Of Atrial Fibrillationmentioning
confidence: 86%
“…11 In the Framingham study in subjects aged 55 to 94 years at baseline the biennial incidence of AF increased with age, ranging from 6.2 and 3.8 cases per 1000 person-examinations in men and women, respectively, aged 55 to 64 years, to 75.9 and 62.8 cases per 1000 person-examinations in men and women aged 85 to 94 years. 3 In the Framingham study arterial hypertension (odds ratio 1.5 in men and 1.4 in women) and diabetes mellitus (odds ratio 1.4 in men and 1.6 in women) emerged as significant independent predictors of AF.…”
Section: Vagaonescu Et Al Atrial Fibrillation In the Shep Studymentioning
confidence: 99%
“…The criteria for inclusion were as follows: (1) the trials were prospective and the findings were published; (2) …”
mentioning
confidence: 99%